Locally driven development: Overcoming the obstacles - Ingram, George (Brookings Institution, 2022)
Locally led development is a complex process that the development comm unity, in the U.S. and around the world, has spent several decades try ing to get right. Yet, despite all the experience and lessons learned, it feels like we are barely beyond the starting line. This publicatio n aims to contribute to the ongoing dialogue on locally led developmen t, especially as to how the United States can address the obstacles po sed by U.S. law, regulation, policy, and practice. It consists of two parts: • An essay by George Ingram that notes the path that has taken us to this point, identifies key obstacles, and invites a discussion o f how to overcome impediments and move forward. • A set of 15 commenta ries written by development experts that add a range of perspectives a nd nuances to the discussion